If it's not what You are looking for type in the equation solver your own equation and let us solve it.
a(2/9)=1/9
We move all terms to the left:
a(2/9)-(1/9)=0
We add all the numbers together, and all the variables
a(+2/9)-(+1/9)=0
We multiply parentheses
2a^2-(+1/9)=0
We get rid of parentheses
2a^2-1/9=0
We multiply all the terms by the denominator
2a^2*9-1=0
Wy multiply elements
18a^2-1=0
a = 18; b = 0; c = -1;
Δ = b2-4ac
Δ = 02-4·18·(-1)
Δ = 72
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$a_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$a_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{72}=\sqrt{36*2}=\sqrt{36}*\sqrt{2}=6\sqrt{2}$$a_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-6\sqrt{2}}{2*18}=\frac{0-6\sqrt{2}}{36} =-\frac{6\sqrt{2}}{36} =-\frac{\sqrt{2}}{6} $$a_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+6\sqrt{2}}{2*18}=\frac{0+6\sqrt{2}}{36} =\frac{6\sqrt{2}}{36} =\frac{\sqrt{2}}{6} $
| 4x^2+6-10=0 | | -x2-5=-35-4x2 | | 5.2+x=60 | | 2(x/5+x/3)-3x/10=3(1/3+2x/5)-1 | | 45=x(.6) | | 70=x(.6) | | Y=-16t^2+70t | | 75=x(.6) | | 5.3×d=42.4 | | 85=x(0.6) | | 2x/3-1/2=1/3(x-7/3) | | x=1+-1^2 | | 100=x(.6) | | y=1+0^2 | | -2.5(1-2n)-1.5n=-2.5+n(5-1.5) | | 4-3-2x/5=7 | | -2.5(1-2n)-1.5n=-2.5-n(5-1.5) | | 2p=p+27 | | -2.5(1-2n)-1.5n=-2.5-6.5n | | 3z-4.5=1,5 | | -2.5(1-2n)-1.5n=-2.5+3.5n | | 8x-14+16=90 | | 10+5n=-25 | | 3x^2+11x-30=0 | | -6+2(3-6b)=84 | | 2(4w-5)=(-2) | | 25=x(0.6) | | -4x-2=-(1-4x) | | —10(9x+7)-1=7(6+2x)-9 | | -2.5(1-2n)-1.5n=-2.5-3.5n | | 96=3(5n-3) | | -3x^2+16x+35=0 |